Aggravating Effects of Psychological Stress on Ligature-Induced Periodontitis via the Involvement of Local Oxidative Damage and NF-κB Activation - Li, Qiang; Zhao, Yajuan; Deng, Daokun; Yang, Jiuhui; Chen, Yongjin; Liu, Jia; Zhang, Min (Mediators of Inflammation, 2022)
Periodontitis is the leading cause of tooth loss in adults, and psychological factors play an important role in the development of periodontitis. To elucidate the adverse effects of psychological stress on the inflammatory process and redox status of periodontitis tissue, fifty male Sprague-Dawley rats were divided into the control, experimental periodontitis, psychological stress, experimental periodontitis plus psychological stress, and experimental periodontitis plus psychological stress plus fluoxetine groups. Chronic unpredictable mild stress (CUMS) was used to establish psychological stress, and silk ligature was used to induce experimental periodontitis. Four weeks later, stressed rats showed altered behaviour, serum hormone levels, and sucrose preference. More obvious alveolar bone loss and attachment loss and higher protein expressions of inflammatory cytokines were observed in the experimental periodontitis plus psychological stress group. The combination of CUMS and periodontitis had synergistic effects on increasing hypoxia-inducible factor-1α (HIF-1α) protein expression and reactive oxygen species (ROS) and malondialdehyde (MDA) contents and decreasing antioxidant enzyme activities compared with those in the stress or periodontitis groups. Moreover, psychological stress further increased p-IκBα and p-NF-κB p65 protein levels and decreased IκBα protein levels in periodontitis rats. Fluoxetine administration alleviated the adverse effects of psychological stress on the progression of periodontitis in rats. These results hint us that psychological stress could aggravate inflammation in periodontitis tissues, which may be partly due to local worsening of oxidative damage and further activation of the nuclear factor kappa-B (NF-κB) signalling pathway.